Integral Inequalities Involving Strongly Convex Functions - Ying-Qing Song; Muhammad Adil Khan; Syed Zaheer Ullah; Yu-Ming Chu (Journal of Function Spaces)
We study the notions of strongly convex function as well as F-strongly convex function. We present here some new integral inequalities of Jensen’s type for these classes of functions. A refinement of companion inequality to Jensen’s inequality established by Matić and Pečarić is shown to be recaptured as a particular instance. Counterpart of the integral Jensen inequality for strongly convex functions is also presented. Furthermore, we present integral Jensen-Steffensen and Slater’s inequality for strongly convex functions.